Contents and evolution of potential furfural compounds in milk-based formula, ultra-high temperature milk and pasteurised yoghurt. (September 2021) - Xing, Qianqian; Fu, Xiaofei; Liu, Zhenmin; Cao, Qing; You, Chunping
Abstract: Potential furfural compounds were detected by reverse phase high performance liquid chromatography (HPLC)-diode array detector (DAD) in milk-based formula (MBF), ultra-high temperature milk (UHT) and pasteurised yoghurt (PY). The content of potential 5-hydroxylmethyl-2-furaldehyde (HMF) and 2-furaldehyde (F) are significantly different in MBF, UHT and PY. 2-Furyl methyl ketone (FMC) and 5-methyl-2-furaldehyde (MF) were not detected in MBF, UHT and PY. Stress testing selected high temperature and high humidity to study the evolution of furfural compounds in MBF, UHT and PY. The contents of potential HMF and F sharply increased under high temperature conditions, while they showed little change under high humidity conditions. Accelerated testing and long-term testing were also conducted. Finally, regression equations of temperature–time-furfural content relationships were derived, by which the contents of furfural compounds in these dairy products stored under certain conditions for a certain time could be predicted.